Cascade reactions of indigo with oxiranes and aziridines: efficient access to dihydropyrazinodiindoles and spiro-oxazocinodiindoles. Issue 33 (7th August 2018) - Butler, Nicholas M.; Hendra, Rudi; Bremner, John B.; Willis, Anthony C.; Lucantoni, Leonardo; Avery, Vicky M.; Keller, Paul A.
Abstract : Cascade reactions of indigo with strained electrophiles affords access to previously unknown oxazocino, pyrazino, and diazepino diindoles with selective anti-plasmodial activity. Abstract : The base-initiated alkylation of the abundant natural dye indigo1 with ring-strained electrophiles results in the unprecedented, one-pot synthesis of functionalised dihydropyrazino[1, 2- a :4, 3- a ′]diindoles, dihydroepoxy[1, 5]oxazocino[5, 4- a :3, 2- b ′]diindoles, and dihydrodiazepino[1, 2- a :4, 3- a ′]diindoles, resulting from intramolecular ring opening-expansion cyclisation processes of their parent oxiranes and aziridines. Regiochemical and stereochemical aspects of the reactions are reported together with integrated mechanistic proposals. This new indigo cascade chemistry should have broad applicability in the synthesis of chemical architectures, not readily-accessible by other means. The three-step synthesis of the useful synthetic precursor ( R )-2-(chloromethyl)-1-tosylaziridine14 is also described. Initial biological activity investigations into these new 2, 2′-dindolyl-based heterocyclic derivatives revealed potent, selective antiplasmodial activity in vitro for several isolated structures, with IC50 values as low as 76.6 nM for (±)-8, while demonstrating low human cell toxicity.